2001
DOI: 10.1007/s004360100412
|View full text |Cite
|
Sign up to set email alerts
|

Anti- Acanthamoeba IgG, IgM, and IgA immunoreactivities in correlation to strain pathogenicity

Abstract: Several representatives of the genus Acanthamoeba are known as causative agents of Acanthamoeba keratitis and granulomatous amoebic encephalitis. These occur predominantly in the immunocompromised host, but it is still unclear what primes the amoebae for pathogenicity. The aim of this study was to assess possible immunological differences between a highly pathogenic and a nonpathogenic Acanthamoeba strain. A total of 20 sera, including two sera of Acanthamoeba keratitis patients, were tested for anti-Acanthamo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…Acanthamoeba densities in Austrian tap water are extremely low and also most Austrian lakes are rather cold and, as far as these data are available, all have very low Acanthamoeba densities (own, unpublished data). However—although usually at low densities—acanthamoebae can be found in almost any habitat and regular contact to them is inevitable, which is also reflected by the fact that almost 100% of the normal population have specific antibodies against acanthamoebae (Walochnik et al 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…Acanthamoeba densities in Austrian tap water are extremely low and also most Austrian lakes are rather cold and, as far as these data are available, all have very low Acanthamoeba densities (own, unpublished data). However—although usually at low densities—acanthamoebae can be found in almost any habitat and regular contact to them is inevitable, which is also reflected by the fact that almost 100% of the normal population have specific antibodies against acanthamoebae (Walochnik et al 2001 ).…”
Section: Discussionmentioning
confidence: 99%
“…genotyping), sub-cultures should be prepared since fungi and other microorganisms also grow very well in these cultures. In addition, several physiological properties can be used to further describe and discriminate Acanthamoeba isolates, including growth rate, temperature tolerance, cell culture pathogenicity and in vivo mouse pathogenicity [ 22 , 24 , 34 , 115 ].…”
Section: Diagnostics Of Akmentioning
confidence: 99%
“…The factors that enable Acanthamoeba to produce disease are not limited solely to the pathogen, but most likely involve host determinants [ 17 , 115 ]. Evidence for this comes from recent studies in the UK, Japan and New Zealand, which suggested that the storage cases of contact lenses of 400–800 per 10,000 asymptomatic wearers are contaminated with Acanthamoeba .…”
Section: Pathogenesis Of Acanthamoeba Keratitismentioning
confidence: 99%
“…However, in some circumstances, they are able to enter human bodies from different sources, colonize some organs, multiply within them, and thus exist as opportunistic parasites causing pathogenic effects. Epidemiological, serological, biochemical, and molecular investigations have shown that people may be exposed to pathogenic as well as nonpathogenic Acanthamoeba strains [ 3 , 6 ]. It seems that the amoebae come into the human body relatively frequently, without pathogenic consequences, as indicated by 50–100% of the healthy population having specific antibodies [ 7 9 ].…”
Section: Introductionmentioning
confidence: 99%